Few and far between: understanding the role of the victim in federal environmental crime prosecutions in the United States - Jarrell, Melissa L. (Crime, law and social change, 2014)
Efforts to gather systematic data and undertake empirical studies on the extent of environmental crime, the magnitude of environmental victimization, and the punishment of environmental offenders in the United States remains elusive in the criminological literature. We take a novel approach to studying these gaps in the literature, by examining federal environmental crime prosecutions. While not all encompassing, this approach advances the literature by providing valuable insights into what types of human victimization occur, the role victims play in prosecutions, and how offenders are punished. What is the nature and extent of case-documented environmental victimization with regard to human victimization in the U.S. over the past decade? We address this question through a content analysis of the Environmental Protection Agency’s (EPA) criminal investigation cases, 2001-11. Out of 972 total criminal cases, we find that only 3 % of cases involve acute or identifiable victimization. Environmental crime victims, unless immediately harmed, are not likely to play a major role in environmental crime cases; thereby limiting potential political and public attention to victims of environmental crime.